2015
DOI: 10.3892/ijo.2015.3203
|View full text |Cite
|
Sign up to set email alerts
|

Targeted silencing of CXCL1 by siRNA inhibits tumor growth and apoptosis in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is an aggressive malignancy and a major cause of cancer-related mortality worldwide. Our previous study shows that chemokine (C-X-C motif) ligand 1 (CXCL1) was upregulated and CXCR1 was downregulated in tumor tissues as compared to peritumor tissues by chemotaxis assay. As the status of CXCL subgroups and their receptors affect progression of HCC, we evaluated potential mechanisms of CXCL1 associated with anticancer effects in HCC based on our previous study. The effects of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Furthermore, CXCL1-mediated myeloid cells infiltration is associated with therapeutic response in breast cancer [ 17 ]. Recently, it has been reported that stably silencing of CXCL1 can inhibit tumor growth in HCC [ 18 ], and knocking down of CXCL1 expression can inhibit tumor growth in colorectal liver metastasis [ 19 ]. Additionally, autocrine and paracrine of CXCL1 can also promote tumor invasion and metastasis [ 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CXCL1-mediated myeloid cells infiltration is associated with therapeutic response in breast cancer [ 17 ]. Recently, it has been reported that stably silencing of CXCL1 can inhibit tumor growth in HCC [ 18 ], and knocking down of CXCL1 expression can inhibit tumor growth in colorectal liver metastasis [ 19 ]. Additionally, autocrine and paracrine of CXCL1 can also promote tumor invasion and metastasis [ 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapy with respect to CXCL1 and CXCR2 has been explored, however, not in the context of nutritional or metabolic modification. In xenograft models, reduced tumor size was observed either when CXCL1 was knocked down by small interfering RNA in HCC cells (36), or when animals were treated with therapeutic T-cells transduced with CXCR2 (37). In conclusion, we demonstrate here a role for palmitate in the up-regulation of an autocrine signaling axis involving CXCL1 and CXCR2.…”
Section: Discussionmentioning
confidence: 69%
“…IL-1β and IL-6 have been shown to be important inflammatory markers upregulated in the kidneys following cisplatin [ 40 ]. Likewise, CXCL1, produced during cisplatin-AKI potentially by T lymphocytes in the kidneys [ 41 ], is a well-known neutrophil chemoattractant capable of inducing apoptosis [ 42 ]. Previous studies report that α7nAChR -/- mice show excessive CXCL1 production and uncontrolled neutrophil infiltration compared to wild-type mice after challenge with immune complexes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%